Wilms Tumor Treatment Outcome in Bangladesh Shishu Hospital & Institute, Dhaka, Bangladesh - Md. Abdul Wohab; Md. Belayet Hossain; Nilufar Akhter Banu Choudhury; Umme Nusrat Ara (Pediatric Review: International Journal of Pediatric Research, 2024)
Background: Wilms tumor is the commonest renal malignancy in childhood. Survival in high-income countries is approximately 90%, whereas in low-income countries, it is less than 60%. This study assessed treatment outcomes of patients with Wilms tumor at Bangladesh Shishu Hospital & Institute.Patients and Methods: We conducted a prospective study in all children diagnosed with Wilms tumor between July 2020 and July 2024. Total 30 patients of Wilms tumor were enrolled in our study, Data were collected  such as treatment outcomes and various socio demographic and clinical characteristics and recorded in sheet.Results: Of the 30 patients with Wilms tumor, 73.33% had event-free survival, 20% had relapsed, 6.67% died. Patients presented as follows-stage I (20%), II (25%), III (35%), IV (15%), or V (5%). The most likely treatment outcome in patients with low-stage (I to II) disease was event-free survival (100%), whereas in those with high-stage (III,IV and V) disease, it was 46.67%.  No deaths or instances of progressive or relapsed disease were recorded among patients with low-stage disease. Stage of disease significantly affected treatment outcomes (P =0 .01) and event-free survival estimates (P < .001). Age at diagnosis, sex, duration of symptoms did not statistically significantly influence treatment outcomes or event-free survival estimates.Conclusion: Survival of patients with Wilms tumor in Bangladesh is lower compared with that in high-income countries. Treatment abandonment is the most common cause of treatment failure. Stage of disease at diagnosis statistically significantly affects treatment outcomes and survival.